Da'wah Communication via Blogging: An Analytical Study on the Role of Blogs in Islamic Preaching - Arifin, Darul; Kholil, Syukur; Soiman, Soiman (Madania: Jurnal Ilmu-Ilmu Keislaman, 2025)
The transformation of digital media has changed the landscape of da'wah communication, encouraging da'i to adapt more relevant and participatory approaches. One platform that attracts attention is that blogs, although not as popular as mainstream social media such as YouTube or Instagram, still have the potential as a text-based and multimedia da'wah communication channel. This research aims to examine the use of blogs as a medium of Islamic da'wah by highlighting the form of interaction, content effectiveness, and communication dynamics between da'i and audiences. This study uses a qualitative approach to the case study method of three Indonesian-language Islamic blogs that have actively published da'wah content in the past year. Data was collected through analysis of blog content, in-depth interviews with blog managers and audiences, as well as participatory observations of the interactions in the comments column. Research shows that da'wah blogs serve as a dialogue space that allows audiences not only to receive religious messages, but also to provide feedback, questions, and discussions. The most effective types of content include practical worship articles, personal inspirational stories, and short video lectures. Two-way interactions and contextual message delivery increase audience involvement and their religious understanding. The study also noted significant challenges such as low comment moderation and the risk of unvalidated dissemination of religious information. The main contribution of this research is to affirm the blog's function as an alternative medium of personal, open, and needs-based da'wah, by integrating the Use and Gratifications theory in analyzing audience motivation.